PENGARUH KOMITMEN ORGANISASI, LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP INTENSI TURNOVER PEGAWAI PADA DINAS PERIKANAN KOTA TANJUNGBALAI - Mahnim Pane; Poltak Parluhutan Simarmata; Nufrizal . (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
The formulation of the problem in this study is: How is the influence of organizational commitment, work environment and job satisfaction on employee turnover intentions at Dinas Perikanan Kota Tanjungbalai. This study aims to determine the effect of organizational commitment, work environment and job satisfaction on employee turnover intentions. With total sampling technique, the sample in this study was 41 people. The results showed; Organizational commitment partially has a positive effect on employee turnover intentions of 3.882; The work environment partially has a positive influence on employee turnover intentions of 2,988; Job satisfaction partially has a positive effect on employee turnover intentions of 2.646; Organizational commitment, work environment and job satisfaction simultaneously have a positive and significant effect on employee turnover intentions of 24,881.